Bioplastics for use in medical industry - Ajp, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Polyhydroxyalkanoates (PHAs) are the bio-based, biodegradable polymers with comparable properties to petroleum-based plastics in many applications.[1] PHA microstructures can be formed in bacterial hosts and findings suggest that PHAs are suitable to develop devices such as hernia repair devices, nerve repair devices, repair patches, cardiovascular patches, adhesion barriers, guided tissue repair and regeneration devices, nerve guides, orthopedic pins, tendon repair devices, bone-marrow scaffolds, tissue engineered cardiovascular devices, other implantable medical devices, such as sutures, meshes, cochlear implants, dental implants, and wound dressings.[2] These materials are biocompatible and can degrade after being implanted that suggest another application in drug release kinetics.